CAPACITY DESIGN OF RC MULTI-STOREY FRAME ACCORDING TO EN 1998-1 - Starčev-Ćurčin, Anka; Lađinović, Đorđe; Radujković, Aleksandra; Rašeta, Andrija (Journal of Applied Engineering Science, 2014)
The method of capacity design requires the ductility of reinforced concrete load-bearing elements and provides the beam plasticity mechanism for a structure to absorb a significant seismic energy. Indeterminate static systems are particularly suitable, where an indefinite number of static indeterminacy determines the number of plastic hinges being forming, thus achieving favourable energy dissipation. In this paper, reinforced concrete five-storey frame is designed for two ductility classes according to the regulations EN1992-1-1 and EN1998-1.
Keywords: Plastic hinges; Ductility; Reinforced concrete frame; Capacity design